2021
DOI: 10.1111/mec.16184
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequencing reveals a complex introgression history and the basis of adaptation to subarctic climate in wild sheep

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 93 publications
2
12
0
Order By: Relevance
“…We further implemented sliding window statistics analysis using the Dsuite v0.5r50 41 to quantify the introgressions. We calculated f dM values using a sliding window of 50 SNPs with a step of 25 SNPs across the genomes with the defined trios (MEN, SSA, O. gmelini _2), where SSA represents the four South-and-Southeast Asian sheep populations suggested to be the introgressed populations by the D -statistics and f 4 -ratio tests.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We further implemented sliding window statistics analysis using the Dsuite v0.5r50 41 to quantify the introgressions. We calculated f dM values using a sliding window of 50 SNPs with a step of 25 SNPs across the genomes with the defined trios (MEN, SSA, O. gmelini _2), where SSA represents the four South-and-Southeast Asian sheep populations suggested to be the introgressed populations by the D -statistics and f 4 -ratio tests.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis was performed using the GTR + GAMMA (4) + I site model and the strict clock model. The most recent common ancestor (MRCA) of Asiatic mouflon and domestic sheep was set to be 0.653 million years [41]. The chain length was set to be 40,000,000 with a burn-in of 2,000,000.…”
Section: Demographics and Divergence Time Inferencementioning
confidence: 99%
“…One of the possible reasons for the selection of this gene in IB camels may be related to the composition of soil and vegetation in the habitat of camels; however, to confirm this claim we need accurate information about these parameters. Previous studies have found that the OPA1 gene, as one of the candidate genes under selection for IB camels, is involved in the adaptation of snow and Tibetan sheep to survive at high altitudes with low oxygen and temperature 47 , 48 , that is somewhat similar to the habitat of IB camels. Also, Tang et al 49 reported that OPA1 potentially enhances the ability of Tibetan chicken to survive under the hypoxic condition of the Qinghai-Tibet Plateau.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding and then maintaining the genetic diversity that exists in domestic livestock breeds is important for the future of agriculture ( Rexroad et al, 2019 ). Recent studies have used WGS to understand and preserve diversity and specific biological traits in breeds that are economically and culturally relevant, including Snow sheep in Siberia and native sheep breeds in Greece ( Upadhyay et al 2021 , and Kominakis et al, 2021). Studies that have used bead array genotypes to analyze diversity between global sheep breeds have demonstrated the geographical distribution and differences of breeds from Europe, Asia, and Africa ( Kijas et al, 2009 and Kijas et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%